Analysis of Decision Number 291/Pdt.G/2024/Pa.Prob Regarding the Revocation of the Mediation Agreement Outside the Presence of the Defendant from the KHI Perspective and Civil Law - Ayu, Fitri; Rusly, Fathullah; Irawan, Ahmad Soni (Civiliza Publishing, 2025)
This study aims to analyze the legal considerations of the panel of judges at the Probolinggo Religious Court in Decision Number 291/Pdt.G/2024/PA.Prob regarding the withdrawal of a mediation agreement in the absence of the defendant, from the perspective of the Compilation of Islamic Law (KHI) and civil law. The background of this research is based on the fact that mediation is a mandatory stage in civil cases, including divorce cases, as stipulated in Supreme Court Regulation Number 1 of 2016. However, in practice, problems arise when a mediation agreement is unilaterally withdrawn without the presence of one party, creating legal implications for the validity of the agreement. This research employs a qualitative method with normative juridical and empirical juridical approaches. Primary data were obtained through interviews with mediators, judges, and litigants, while secondary data were sourced from laws and regulations, legal literature, and case documents. The findings reveal that the withdrawal of a mediation agreement without the presence of the defendant has the potential to violate the principles of balance and good faith in agreements as regulated in Article 1338 of the Indonesian Civil Code. From the perspective of KHI, such an action is inconsistent with the principles of deliberation and amicable settlement as stipulated in Articles 115 and 116 of KHI. The panel of judges in this decision considered the existence of procedural violations in the withdrawal process, thereby declaring the mediation agreement non-binding. These findings emphasize the importance of the presence of both parties in the mediation and agreement withdrawal process to ensure legal certainty and substantive justice.